Good parental feeding style reduces the risk of stunting among under-five children in Yogyakarta, Indonesia - Erni Gustina; Liena Sofiana; Suci Musvita Ayu; Yuniar Wardani; Ditra Irna Lasari (Universitas Udayana, 2020)
Background and purpose: In Indonesia, many studies on thecauses of stunting in children have been conducted. However, still few have explored the parental feeding style in relation to stunting. The purpose of this study was to analyze the relationship between parental feeding style and stunting among under-five children in Kulon Progo District, Yogyakarta. Methods: This study used a cross sectional design. This study involved 729 respondents who were the entire population of under-five children in Kulon Progo. Mothers were interviewed about the socio-demographic, economic and parental feeding style that mothers gave to their children using a structured questionnaire. Data were analyzed descriptively to identify the frequency distribution of each variable, hypothesis testing with chi square test and multivariable analysis with logistic regression at asignificance level of 5% were performed. Results: Of the 729 under-five children analyzed, 37.6% werefound to be stunting. The proportion of poor parental feeding style was almost 50%. The finding of this study showed that mother’s occupation (AOR=2.13; 95%CI: 1.26 3.59), family income (AOR=3.56; 95%CI: 2.34-5.42) and parental feeding style (AOR=2.77; 95%CI: 1.97-3.91) have a significant relationship with stunting. Conclusion: The prevalence of stunting is quite high in the study area. Parents with poor parental feeding style are predicted to increase the risk of stunting among under-five children. Familybased interventions that involve parenting styles in child feeding practices should be considered in reducing stunting among children.